2020
DOI: 10.1002/spe.2883
|View full text |Cite
|
Sign up to set email alerts
|

Usability implications in software architecture: The case study of a mobile app

Abstract: Usability is a highly desired but often ignored software quality. Effective user interfaces tend to increase learnability, effectiveness and user satisfaction. But usability is often neglected in the early stages of software development and is thus frequently not address in a system's architectural design. Furthermore, because usability is often neglected or deferred, it is difficult to estimate the effort specifically spent on adding or improving usability mechanisms in the software architecture and in code. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Some of the experimental studies evaluate or validate applications or final products focus on web applications [31]- [34], some address mobile applications [35], [36], and some evaluate specific properties like security [37], comprehension and learnability [38] or application programming interfaces (APIs) [39]. A case study of the impact on mobile application architecture and implementation design of seven usability mechanisms, including ABR and PFB, is reported in [18]. They conclude that the mechanisms affect the overall design, and end-user satisfaction can be improved through different combinations of mechanisms.…”
Section: Usability Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the experimental studies evaluate or validate applications or final products focus on web applications [31]- [34], some address mobile applications [35], [36], and some evaluate specific properties like security [37], comprehension and learnability [38] or application programming interfaces (APIs) [39]. A case study of the impact on mobile application architecture and implementation design of seven usability mechanisms, including ABR and PFB, is reported in [18]. They conclude that the mechanisms affect the overall design, and end-user satisfaction can be improved through different combinations of mechanisms.…”
Section: Usability Experimentsmentioning
confidence: 99%
“…We chose these three mechanisms because they had a greater impact on software design [12]. This impact was identified in earlier studies on usability mechanisms [5], [18]. In both cases, there is evidence that a significant design-level effort is required to include the functionalities associated with the mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because usability is frequently overlooked or postponed, estimating the time and effort spent especially on adding or improving usability mechanisms in software architecture and code is difficult. As a result, this led to a mobile development challenge [110].…”
Section: Ignorance Of Usabilitymentioning
confidence: 99%
“…S1 a and S2 a of FQFD a are used in this phase. Following an informed discussion among a small group of five manufacturing engineers and a review of SPC and software requirement literature, 48,49 nine URs are identified (Table 2).…”
Section: Requirement Analysis Phasementioning
confidence: 99%